NILAI PELANGGAN DAN MINAT LOYALITAS - Hutama, Dhagat Wihasta; Widiyanto, Ibnu (Diponegoro Journal of Management, 2015)
Playing futsal is increasingly popular. Many people play in the rental field. Dewa Futsal is one of the futsal court rental place in Semarang. This study aims to determine whether the speed of service, convenience of location and price perception has an influence on the value of the customers that have an impact on the interest of loyalty to Dewa Futsal Semarang. The samples used in this study were 400 people who had rented a field in god Futsal Semarang. The questionnaire distributed in June 2015 to July 2015. The data were processed using multiple regression analysis. The results showed that all three independent variables have positive and significant influence on the variable value of the customer. Value of the customers variable have a positive and significant effect on the interest of loyalty variable and acts as an intervening variable.